The Cambridge world history of genocide: Volume III: Genocide in the contemporary era, 1914-2020 - Kiernan, Ben; Lower, Wendy; Naimark, Norman M.; Straus, Scott (Cambridge histories online, 2023)
Volume III examines the most well-known century of genocide, the twentieth century. Opening with a discussion on the definitions of genocide and 'ethnic cleansing' and their relationships to modernity, it continues with a survey of the genocide studies field, racism and antisemitism. The four parts cover the impacts of Racism, Total War, Imperial Collapse, and Revolution; the crises of World War Two; the Cold War; and Globalization. Twenty-eight scholars with expertise in specific regions document thirty genocides from 1918 to 2021, in Europe, the Middle East, Africa, Asia, and Latin America. The cases range from the Armenian Genocide to Maoist China, from the Holocaust to Stalin's Ukraine, from Indonesia to Guatemala, Biafra, Bangladesh, Cambodia, Bosnia and Rwanda, and finally the contemporary fate of the Rohingyas in Myanmar and the ISIS slaughter of Yazidis in Iraq.